PERAN BUMDES DALAM PENYEDIAAN PUPUK PADA KEGIATAN BUDIDAYA PADI SAWAH DI DESA WULANGA JAYA KECAMATAN TIWORO KEPULAUAN KABUPATEN MUNA BARAT - Tias Ramadani; Anas Nikoyan; Yoenita Jayadisasta (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
This study aims to ascertain the role of the Business Management and Services (BUMDes) entity in the provision of fertilizers utilized in paddy rice cultivation activities in Wulanga Jaya Village, Tiworo Islands Sub-district, West Muna Regency.The present research utilizes a qualitative approach. The selection of informants was conducted using purposive techniques, resulting in a total of 26 individuals included in this study. These informants included administrators, members of the BUMDes, and four farmer groups, as well as the village government and the Field Agricultural Extension (PPL). Data collection methods included observation, in-depth interviews, and documentation using an interview guide. The present study focuses on the role of BUMDes in the provision of fertilizer to wet-rice farming, which includes facilitator, mediator, and motivator. The collected data underwent analysis using a qualitative descriptive analysis method, which involves processing the data through three stages: data reduction, data presentation, and verification/conclusion drawing. The results of the study indicated that the role of BUMDes in the provision of fertilizer in paddy rice cultivation activities in Wulanga Jaya Village encompasses the roles of facilitator, mediator, and motivator. Specifically, the role of BUMDes as a facilitator includes supply management and partnership, while its role as a mediator encompasses distribution and service. Furthermore, the role of BUMDes as a motivator can be observed from the satisfaction of farmers in the process of providing fertilizer.